(untitled) (Research, Society and Development, 2020)
Objective: to investigate the influence that the training process of nursing has on the use of the ventrogluteal site for intramuscular injections. Methods: this is an exploratory, qualitative and quantitative study, 23 semi-structured interviews were conducted in the period from October to November 2017. Results: it was found that during the training of 47.83% of the interviewees, the four sites for intramuscular injection were approached, whereas for 52.17% the Hochstetter Technique was not addressed. Regarding the frequency of use of the Ventro Gluteal region for intramuscular administration, 82.61% of the interviewees stated that they never used the region and 17.39% used it, but without frequency. Final considerations: there is a need to review the way of teaching intramuscular medication administration during the training of nursing. It becomes essential to increase students’ autonomy and provide the insertion of the Hochstetter technique in practice to the use of active teaching methodologies in nursing.